2003
DOI: 10.1120/jacmp.v4i4.2502
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing an electronic portal imaging device to monitor light and radiation field congruence

Abstract: A method to investigate light and radiation field congruence utilizing a commercially available amorphous silicon electronic portal imaging device (EPID) was developed. This method employed an EPID, the associated EPI software, and a diamond‐shaped template. The template was constructed from a block tray in which Sn/Pb wires, 1 mm in diameter, were embedded into a diamond shaped groove milled into the tray. The collimator jaws of the linac were aligned such that the light field fell directly on the corners of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…EPID has been shown as a useful QA tool to perform this test. 11,12 In the EPID-based approach, images of different MLC square field sizes through the custom designed phantom are acquired and automatically analyzed to quantify the field size. This test relies on the visual verification of light field position against the embedded steel-spheres on the phantom.…”
Section: E2 Collimating System Checksmentioning
confidence: 99%
See 1 more Smart Citation
“…EPID has been shown as a useful QA tool to perform this test. 11,12 In the EPID-based approach, images of different MLC square field sizes through the custom designed phantom are acquired and automatically analyzed to quantify the field size. This test relies on the visual verification of light field position against the embedded steel-spheres on the phantom.…”
Section: E2 Collimating System Checksmentioning
confidence: 99%
“…Earlier studies have shown the utility of EPIDs for routine linac QA and dose measurements. 5,6 EPIDs have been used for verification of beam flatness and symmetry, 7 MLC leaf position, 8,9 linac isocenter position, 10 coincidence of the light field and radiation field, 11,12 collimator and couch axis of rotation, 13 leaf gap measurements, 14 beam output, and assessment of jaw alignment. 15 With sub-millimeter spatial resolution, EPIDs are well suited for IMRT plan verification and portal dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…This test can also be performed using EPID with an object opaque for both light and radiation fields. (65)(66)(67) The Picket Fence test can be also accomplished using a film or an EPID. (68) While the radiation is on, a dynamic MLC plan is executed, which continuously moves the abutted leaf ends from one side to the other while halting at designated locations for several seconds.…”
Section: A2 Mlc Commissioningmentioning
confidence: 99%
“…Megavoltage (MV) electronic portal imaging device (EPID) has been widely used as an on‐line verification tool for treatment field in radiation therapy 1, 2, 3, 4. While the weight of the verification tool appears to be decreased after the emergence of kilovoltage (kV) imager mounted on a linear accelerator, EPID images still have their own advantages.…”
Section: Introductionmentioning
confidence: 99%